SLEEP AND PHYSICAL PERFORMANCE IN DISABLED LOW-INCOME OLDER WOMEN. (11th November 2018) - Okoye, S; Szanton, S; Nkimbeng, M; Perrin, N; Spira, A
Abstract: Sleep disturbances are common in older adults and have been associated with indicators of physical disability, including slower gait speed and difficulty with self-care activities. Further understanding of the relationship between sleep disturbances and disability may contribute to development of interventions to reduce or prevent later-life disability. Few studies have examined the relationship between sleep disturbances and physical disability in low-income, or African-American older adults using objective measures of both sleep and physical performance. We determined the cross-sectional association between sleep parameters, measured by wrist actigraphy, and scores on the Short Physical Performance Battery (SPPB) in a sample of 129 disabled, low-income, predominantly African-American older women (92.25% African-American; 75.0 ± 7.4 years of age, 81% high school education or less) with Mini Mental Status Examination scores ≥24. Primary predictors were total sleep time (TST; total number of minutes in bed spent asleep), wake time after sleep onset (WASO; total number of minutes spent awake after initially falling asleep), and sleep efficiency (SE; % time in bed spent asleep); SPPB scores were the outcome. Each 30-minute increase in TST was associated with a 0.23-point better score on SPPB after adjustment for demographic characteristics and health conditions (b = 0.23, p=0.01). Neither WASO nor SE were significantly associated with SPPB scores. Findings suggest objectively measured longer TST is associated with better physical performance in disabled, low-income older women. Further research should examine longitudinal associations between sleep disturbances and disability in low-income and African-American older adults.